Taylor's clinical nursing skills : a nursing process approach - Lynn, Pamela Barbara (Philadelphia : Lippincott Williams & Wilkins, 2008)
Details the skills identified in "Taylor's Fundamentals of Nursing, Sixth Edition" and describes additional advanced skills. This title outlines the procedures and skills in a step-by-step manner, with rationale, and offers guidance on how to respond to unanticipated outcomes
Rev. ed. of: Taylor's clinical nursing skills / [edited by] Pamela Evans-Smith. c2005. To accompany: Fundamentals of nursing / Carol Taylor ... [et al.]. 6th ed. c2008 [1 CD]
NUR
Keywords: Nursing; Nursing process; Nursing care -- Methods